Career decision self-efficacy of Indonesian students - Khatijatusshalihah Khatijatusshalihah; Irin Riamanda; Eka Dian Aprilia; Haiyun Nisa (Institut Agama Islam Negeri Langsa, 2022)
Early adulthood is one of the crucial moments of an individual’s life since it marks a person’s thinking seriously regarding the future, especially in careers. An individual will firstly make a series of career decisions before choosing a career. Self-efficacy is the best predictor of students’ academic and social integration. This study used a quantitative method with a descriptive analysis approach to describe and identify the status of career decision-making self-efficacy students in preparing for career decisions. Participants of the current study were 196 students from different backgrounds such as genders, choice of majors, domiciles, and types of accommodation. Participants were selected using a simple random sampling technique. The instrument used is Career Decision Self Efficacy. The findings revealed that 70.9 % of the students are in a high level of Career Decision Self Efficacy (M= 98.9), and there were no differences in Career Decision Self Efficacy among students reviewed based on genders, and choice of majors, domiciles, and types of accommodations.